Relationship Between Adiponectin Levels and Cognitive Function in Elderly Patients with Obesity in RSUD Dr. Mohamad Soewandhie Surabaya - Salwa Salsabila; Rahajoe Imam Santoso; Hernycane Sosilya (International Journal Of Health Science, 2026)
Obesity in the elderly is an increasingly prevalent condition and is associated with a higher risk of metabolic disorders and cognitive decline. Adiponectin, an adipokine with anti-inflammatory and neuroprotective properties, is thought to play a role in maintaining cognitive function through the regulation of metabolism and inflammatory responses. However, scientific evidence regarding the association between adiponectin and cognitive function among obese elderly individuals in Indonesia remains limited. This study aimed to describe adiponectin levels, cognitive function, and the relationship between the two among obese elderly patients at RSUD dr. Mohamad Soewandhie Surabaya. This study employed an analytic observational design with a cross-sectional approach and involved obese elderly respondents selected using a total sampling technique. Adiponectin levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method, while cognitive function was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). Data analysis was performed using the Shapiro–Wilk normality test and Spearman’s rho correlation test. The results showed a statistically significant relationship between adiponectin levels and cognitive function among obese elderly individuals (p = 0.731; r < 0.01). In conclusion, this study found that adiponectin levels were associated with cognitive function in the obese elderly population examined.